O Partido Comunista (1922-1962): lugar de memória, espaço de disputa - Souza, Vital Nogueira de (2007)
This work studies the dispute by Party Communist s memory in Brazil during and after division which it resulted in the appearance of two parties entitled communists, in the brazilian political context, in the final of the fifties and beginning of the sixties: the Brazilian Communist Party (in Portuguese, Partido Comunista Brasileiro) and the Communist Party of Brazil (in portuguese, Partido Comunista do Brasil). Along of yours three chapters, the author tries to answer some questions as: what were the elements which constituted the Communist Party s memory, in the period from 1922 to 1956? At which moment did this memory pass to be fiercely contested? Who and which documents reveal this? How did it happen the dispute by this memory? The approach to topic consider which the production of memory by Communist Party and the dispute for your possession by communists of PCB and of PCdoB happened in scope of national reality and of party, spaces notions understand from concept of memory developed for authors as Halbwachs, Le Goff, Pollack and Pierre Nora. To explain the objectives of historical research it has used as methodology the exam and the interpretation of documentary and bibliographical sources, with priority for the party s documents then it was depicted a collective interpretation about the events considered more importants. The sites of Partido Comunista do Brasil (www.pcdob.org.br or vermelho.org.br) and of Partido Popular Socialista (www.pps.org.br) also went consulted